2014
DOI: 10.1108/he-11-2013-0055
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting schools: consensus, strategies, and potential

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…Examining the school environment by assessing both the physical sanitary conditions as well as the schools deworming practices revealed crucial information and our results lend support to WHO’s Health promoting schools (HPS) initiative [86]. In terms of STH infections, greater consideration should be given to schools as either potential enablers of transmission or as crucial players in their control.…”
Section: Discussionsupporting
confidence: 53%
“…Examining the school environment by assessing both the physical sanitary conditions as well as the schools deworming practices revealed crucial information and our results lend support to WHO’s Health promoting schools (HPS) initiative [86]. In terms of STH infections, greater consideration should be given to schools as either potential enablers of transmission or as crucial players in their control.…”
Section: Discussionsupporting
confidence: 53%
“…Africa’s youth are the next generation of parents and are still able to modify their individual NCD trajectories. DOHaD-informed knowledge and health practices need to be integrated into school curricula and other youth-oriented arenas, using compelling messaging and novel means of engagement [18]. …”
mentioning
confidence: 99%
“…Concrete activities such as "rocking a stuffed animal to sleep while breathing" (Kaiser Greenland, 2010) or "sitting still like a frog" (Snel, 2013) Research into the effectiveness of school-based interventions is burgeoning. While much of this work has focused on the effectiveness of discrete interventions, there is now a growing interest in developing a broader understanding of the characteristics of successful schoolbased mental health initiatives (Macnab et al, 2014;Rowling, 2009;Stewart-Brown, 2006;Weare and Nind, 2011;Wells et al, 2003). For instance, Weare and Nind (2011) reviewed 52 existing reviews and found that, in general, school-based mental health interventions had small-to-moderate, short-term positive effects on a range of mental health, social, emotional and educational outcomes.…”
Section: Mindfulness Friends For Lifementioning
confidence: 99%